Intraband carrier dynamics in Landau-quantized multilayer epitaxial graphene - Mittendorff, Martin; Orlita, Milan; Potemski, Marek; Berger, Claire; de Heer, Walter A; Schneider, Harald; Helm, Manfred; Winnerl, Stephan (New journal of physics, 2014)
We investigate the low-energy carrier dynamics in Landau quantized multilayer epitaxial graphene on SiC, using 14 meV photons. The THz absorption is dominated by Landau-level transitions within the conduction bands of several graphene layers with different doping. Varying the magnetic field allows us to tune the THz-induced response from induced transmission around B = 0 to induced absorption at intermediate fields (1.5 T-3.3 T) and back to induced transmission at higher fields (3.3 T-7 T). The main features of this complex response are explained by a strong dependence of the absorption on the electron temperature. Furthermore a prolonged relaxation at high fields, which is attributed to reduced scattering via optical phonons, is observed.